2012
DOI: 10.1111/irv.12065
|View full text |Cite
|
Sign up to set email alerts
|

Factors promoting the prolonged shedding of the pandemic (H1N1) 2009 influenza virus in patients treated with oseltamivir for 5 days

Abstract: BackgroundThe duration of viral shedding is an important determinant of infectivity and transmissibility and provides vital information for effective infection prevention and control. However, few studies have evaluated viral shedding in patients admitted to hospital with 2009 H1N1 influenza and treated with oseltamivir.ObjectiveTo determine the incidence of prolonged 2009 H1N1 influenza viral shedding in patients treated for 5 days with oseltamivir and to identify factors that promote prolonged viral shedding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…However, data on factors associated with prolonged shedding of respiratory viruses is limited with the exception of influenza virus in mainly immunocompetent populations and coronavirus in HCT recipients. 9, 26, 27 The present study showed initial high viral load was a risk factor for prolonged HRV shedding in HCT recipients, consistent with our previous study of coronavirus. 9…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, data on factors associated with prolonged shedding of respiratory viruses is limited with the exception of influenza virus in mainly immunocompetent populations and coronavirus in HCT recipients. 9, 26, 27 The present study showed initial high viral load was a risk factor for prolonged HRV shedding in HCT recipients, consistent with our previous study of coronavirus. 9…”
Section: Discussionsupporting
confidence: 92%
“…Viral shedding duration is often used as an endpoint in clinical trials of new antivirals [23] , [24] , [25] , and identifying risk factors for prolonged shedding is thus critical for appropriate stratification of patients in randomized trials. However, data on factors associated with prolonged shedding of respiratory viruses are limited, with the exception of influenza virus in mainly immunocompetent populations and coronavirus in HCT recipients [9] , [26] , [27] . The present study showed initial high viral load was a risk factor for prolonged HRV shedding in HCT recipients, consistent with our previous study of coronavirus [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Quantifying influenza shedding duration, a possible predictor of infectivity and transmissibility, can inform infection prevention and control measures [1]. Several factors, such as age and to a lesser extent human immunodeficiency virus (HIV) status, have been found to impact shedding duration [2, 3].…”
mentioning
confidence: 99%
“…Respiratory virus positivity in respiratory specimens is generally up to 14 days in most series; however, virus can remain positive for several months despite resolution of symptoms [13,23,28]. In one study, corticosteroid dosages greater than 1 mg/kg daily were shown to prolong influenza virus positivity compared to persons treated with lower doses (15 vs 9 days) [17].…”
Section: Clinical Presentationmentioning
confidence: 99%